2014
DOI: 10.2190/hs.44.3.j
|View full text |Cite
|
Sign up to set email alerts
|

Failing Ethics 101: Psychologists, the U.S. Military Establishment, and Human Rights

Abstract: The American Psychological Association (APA) has long maintained a close, even symbiotic, relationship with the Department of Defense (DOD) and the Veterans Administration (VA). Herein we highlight these close ties and describe psychologists' participation in interrogations by U.S. military and intelligence entities. We then review the APA's statements about the permissibility of psychologist participation in the interrogation and torture of suspected terrorists. These issues are significant in and of themselv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…It may also have caused concern to DCTs to consider that their curriculum possibly failed to prepare students for ethical dilemmas in military settings. Still, what DCTs reported about their educational offerings are entirely consistent with what graduate students themselves reported in 2014 (Boyd et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It may also have caused concern to DCTs to consider that their curriculum possibly failed to prepare students for ethical dilemmas in military settings. Still, what DCTs reported about their educational offerings are entirely consistent with what graduate students themselves reported in 2014 (Boyd et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…But even in 2015, such education was not required by APA, and was generally lacking. A survey of psychology graduate students published two years ago found that those students received very little instruction in military medical ethics, did not know about the existence of the HCPDS, and were largely unfamiliar with the mandates of international ethical standards and agreed upon conventions (Boyd et al, 2014). Given how little these students reported being instructed in issues of military medical ethics, we thought to further explore this issue by examining whether psychology graduate programs believed they were teaching students about ethical dilemmas in military settings.…”
Section: Why Did Psychologists Fail To Disobeymentioning
confidence: 99%
“…Boyd et al (2014) and other authors involved in the American Psychological Association’s Guantanamo, Abu Ghraib, etc. torture debate have highlighted the issue that psychologists affiliated with armed forces are particularly prone to adopt unethical professional conduct by conforming to military rules.…”
Section: Comparative Aspects Discussion and Implicationsmentioning
confidence: 99%
“…Under some historical conditions or circumstances and contexts, psychologists and psychological knowledge were in danger of being abused by political powers, largely for clandestine purposes, such as conducting torture or the persecution of political opponents. These abuses became apparent after World War II, during the time known as the “Cold War” in the 1950s and 1960s, as well as in more recent discussions about the involvement of U.S. psychologists into torture (Boyd, LoCicero, Malowney, Aldis, & Marlin, 2014; Costanzo, Gerrity, & Brinton Lykes, 2007; Haritos-Fatouros, 2003; Hoffman et al, 2015; Pope, 2016). The open intelligence or secret police archives of the former East German Stasi (abbreviation for “ Staatssicherheit ”—state security) provide an abundance of material on a unique example of such abuses of psychology.…”
mentioning
confidence: 99%
“…Im Gegensatz dazu haben die meisten nationalen und vor allem internationalen Berufsdachorganisationen eindeutig klargestellt, dass jede Unterstützung oder Mitarbeit bei Folter durch ihre Berufsmitglieder eine schwere Verletzung der Berufsethik darstellt. Insbesondere der Weltärzteverband sowie der Weltpsychiatrieverband haben diesbezüglich immer wieder eindeutig Stellung bezogen (Perez-Sales et al 2018;Wilson 1983;Helmchen & Okasha 2000), während der amerikanische Psychologenverband erst sehr verzögert und nach heftiger internationaler Kritik reagierte (Bohannon 2015;Boyd et al 2014;Olson et al 2008).…”
Section: Die Rolle Von Gesundheitsberufen Im Bereich Des Menschenrechunclassified